Genotyping and Antibiotic Resistance Traits in Campylobacter jejuni and coli From Pigs and Wild Boars in Italy - Marotta, Francesca; Di Marcantonio, Lisa; Janowicz, Anna; Pedonese, Francesca; Di Donato, Guido; Ardelean, Adrian; Nuvoloni, Roberta; Di Giannatale, Elisabetta; Garofolo, Giuliano (Frontiers in Cellular and Infection Microbiology, 2020)
The present study investigated the genomic constitution and antimicrobial resistance (AMR) of 238 Campylobacter from pigs and wild boars in Italy between 2012 and 2019. Campylobacter strains were genotyped using multilocus sequence typing (MLST) and whole genome MLST (wgMLST), screened for antimicrobial resistance genes, and tested for phenotypic susceptibility to six different antibiotics. C. coli was detected in 98.31% and 91.66% of pigs and wild boars, while C. jejuni was isolated in the remaining cases. MLST assigned 73 STs and 13 STs in pigs and wild boars, respectively, including 44 novel STs. The predominant ST in pigs was ST-854 (12.36%), followed by ST-9264 (6.18%). ST-1055 and ST-1417 were predominant in wild boars (30% and 13.33%, respectively). The minimum spanning tree using 1,121 global MLST profiles showed specific Italian clusters and a clear separation between pig and wild boar profiles. The wgMLST confirmed the MLST clustering and revealed a high genetic diversity within C. coli population in Italy. Minimum inhibitory concentrations (MIC) of six antibiotics revealed higher resistance in pigs to ciprofloxacin, nalidixic acid, streptomycin and tetracycline, compared to wild boar. In contrast, most strains were susceptible to gentamicin. Worrying levels of multidrug resistance (MDR) were observed mostly in pig isolates. Molecular screening of AMR mechanisms revealed the predominance of gyrA T86I substitution among fluoroquinolone- and quinolone-resistant isolates, and the 23S rRNA A2075G mutation among macrolide-resistant isolates. Other resistance determinants were observed: (i) tet(O) gene was present among tetracycline-resistant isolates; (ii) rpsL and aph(3’)-III genes conferring resistance to aminoglycosides, were identified only in streptomycin or gentamicin-resistant pig isolates; (iii) cmeA, cmeB, cmeC, cmeR genes responsible of pump efflux mechanisms, were observed in almost all the strains; (iv) OXA-61, encoding β-lactamase, was found in the half of the strains. Genotypic and phenotypic AMR profiling was fairly correlated for quinolones/fluoroquinolones. Campylobacter infection is common also in wild boar populations in Italy, suggesting that wild boars could be a reservoir of resistant and multi-resistant Campylobacter species, which may be of public health concern. The present study adds to our knowledge on the epidemiological and ecological traits of this pathogen in domesticated and wild swine.